The influence of management practices on service recovery performance, turnover intention and job satisfaction among front line officer in the public sector organisation in Jordan - Sakher A I Al-Bazaiah; Hashim Hassan; Ilham Sentosa (Proceedings of AICS - Social Sciences, 2017)
This study considers that management practices have the ability to turn dissatisfied customers to loyal customers through effective service recovery encounter. For this purpose, this study investigates the potential impact of selected management practices on service recovery performance and its outcomes of front line officers by adapting Boshoff and Allen, (2000) research model. Using Boshoff and Allen, 2000 instrument, 147 front line officers who involve with electronic government (E-Gov) were analyzed about their perceptions about public sector organisation management practices. Quantitative approach using multivariate data analysis such as descriptive analysis, reliability analysis and multiple regressions through SPSS version 24.00 were used to estimate the predictors and its consequences of service recovery performance in the public sector organization (PSO) in Jordan. Results shows that ‘affective organizational commitment’ exert a strong positive relationship compared with customer service training, empowerment and supervisor support. The variable role ambiguity shows a weak non-significant relationship as opposed to the proposed effect. Results also suggest that successful service recovery performance leads to increased job satisfaction and decreased turnover intentions. This study could be generalized as a main guideline for public sector organization in Jordan. Moreover, the responses were collected from same participants asking about their performance, which may result in bias of common variance. Furthermore, this study makes contribution both academically and practically. Practically, the findings indicate the organizational behavior variables that the manager has to take care to achieve front line service recovery excellence. Academically, this study is unique as it focuses on public sector organisation (PSO) facing sudden completion due to deregulation as a case in point.